Pilihan Profesi Akuntan (Survei Terhadap Mahasiswa Akuntansi Di Palembang) - Lia Sari; Irsan; Hilwa Anggraini; Nelly; Roy Saleh (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2019)
This study aims to determine the choice of accountant profession from the perceptions of accounting students in Palembang. The sampling used convenience sampling, with a total of 358 accounting student respondents from 8 universities in the city of Palembang in 2019. The variables that are thought to affect the career choices of accountants from accounting students in Palembang are variables of Gender, Previous School, Degree of Study in University, and Occupation. Meanwhile, the reasons that are thought to be the background of the choice of the accounting profession by students include financial / income awards, career opportunities, job market opportunities, social values, and job flexibility. The dependent variable is the choice of the accounting profession, including Public Accountants, Internal Accountants, Government Accountants, and Educating Accountants. Hypothesis testing uses Chi-Square analysis and ranking. The results of the analysis show that the most chosen professions are Corporate Internal Accountants, Public Accountants, Government Accountants, and Educator Accountants in the last position. Only the Degree of Study in University and Occupation variables differ significantly in the choice of accountant profession, while the variables of Gender and School Origin are not significantly different in the choice of accountant profession. The reasons behind the choice of accountant career by accounting students are mainly the reasons for income, career opportunities, job market opportunities, job flexibility, and social values.